2020
DOI: 10.1021/jasms.0c00377
|View full text |Cite
|
Sign up to set email alerts
|

Sulfolane-Induced Supercharging of Electrosprayed Salt Clusters: An Experimental/Computational Perspective

Abstract: It is well-known that supercharging agents (SCAs) such as sulfolane enhance the electrospray ionization (ESI) charge states of proteins, although the mechanistic origins of this effect remain contentious. Only very few studies have explored SCA effects on analytes other than proteins or peptides. This work examines how sulfolane affects electrosprayed NaI salt clusters. Such alkali metal halide clusters have played a key role for earlier ESI mechanistic studies, making them interesting targets for superchargin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…We observed the entire series of HS(MoS 3 ) N 1− from N = 1–8 only when a relatively high concentration of (NH 4 ) 2 MoS 4 solution (≈10 m m ) was electrosprayed, by taking advantage of the notion that high concentration promotes cluster formation. [ 49,50 ] Out of the observed MoS ion series, only HS(MoS 3 ) 1− and HS(MoS 3 ) 3 1− have been previously observed, where HS(MoS 3 ) 1− is a typical ion observed from solutions of MoS 4 2− salts, [ 51 ] while HS(MoS 3 ) 3 1− has been observed from gas phase dissociation of HMo 3 S 13 − ions. [ 52 ] We chose to study heavy MoS ions (HS(MoS 3 ) N 1− , N ≥ 4) due to their higher adsorption energies on graphene, which allow them to adhere to graphene stronger and to be retained on graphene long enough to form the nanoribbons (Figures S1 and S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed the entire series of HS(MoS 3 ) N 1− from N = 1–8 only when a relatively high concentration of (NH 4 ) 2 MoS 4 solution (≈10 m m ) was electrosprayed, by taking advantage of the notion that high concentration promotes cluster formation. [ 49,50 ] Out of the observed MoS ion series, only HS(MoS 3 ) 1− and HS(MoS 3 ) 3 1− have been previously observed, where HS(MoS 3 ) 1− is a typical ion observed from solutions of MoS 4 2− salts, [ 51 ] while HS(MoS 3 ) 3 1− has been observed from gas phase dissociation of HMo 3 S 13 − ions. [ 52 ] We chose to study heavy MoS ions (HS(MoS 3 ) N 1− , N ≥ 4) due to their higher adsorption energies on graphene, which allow them to adhere to graphene stronger and to be retained on graphene long enough to form the nanoribbons (Figures S1 and S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…For the electrospray ionization, (NH 4 ) 2 MoS 4 or (NH 4 ) 2 WS 4 solutions with an elevated concentration (10 mm in 1:1 water:isopropyl-alcohol) were used to promote the condensation of the Mo or W species in the generated electrospray microdroplets, as suggested by refs. [49,50] Using the ESIBD technique, described in detail elsewhere, [73] the negative ions obtained from the electrospray were characterized by using a home-built time-of-flight mass spectrometer, mass-selected using the quadrupoles, and aimed onto the surface (e.g., graphene on a TEM grid) held at room temperatures in a high vacuum (HV) chambers of 10 −7 mbar. The intact landing of the deposited MoS or WS ions was ensured by applying a voltage on the surface which would decelerate the incident ions to a low kinetic energy of ≈3 eV, considered to be well in the range of "soft landing".…”
Section: Methodsmentioning
confidence: 99%
“…Increasing the charge states of proteins is another tactic typically enabled by addition of solution modifiers prior to ESI resulting in the production of “supercharged” ions. Examples of commonly used supercharging agents include m -nitrobenzyl alcohol, sulfolane, and ethylene carbonate, among others. The mechanism of supercharging is still under investigation. The use of these agents can improve mass spectrometry analyses of proteins by shifting the m / z of the ions to a less congested region, separating overlapping ions, in some cases consolidating ion current into fewer charge states or increasing fragmentation efficiency during MS/MS.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of commonly used supercharging agents include m-nitrobenzyl alcohol, sulfolane, and ethylene carbonate, among others. [45][46][47] The use of these agents can improve mass spectrometry analyses of proteins by shifting the m/z of the ions to a less congested region, separating overlapping ions, in some cases consolidating ion current into fewer charge states, and/or increasing fragmentation efficiency during MS/MS. The mechanism of supercharging is still under investigation; however, some possible explanations are based on an increase in solvent surface tension which can lead to production of more highly charged droplets, and increased solvent polarity which may stabilize charge sites.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of supercharging is still under investigation; however, some possible explanations are based on an increase in solvent surface tension which can lead to production of more highly charged droplets, and increased solvent polarity which may stabilize charge sites. [42][43][44][45][47][48][49] Supercharging may also lead to significant changes in protein fragmentation, offering the potential to increase the information harvested from top-down MS/MS analysis. For example, one study showed that supercharging can result in the funneling of fragmentation into a few dominant backbone cleavages while reducing the abundance of fragmentation at neighboring residues.…”
Section: Introductionmentioning
confidence: 99%